Discussion of 5G satellite dual-mode terminal requirement and application in the integration communication scenario of satellite and UTRAN - Wenzhe WANG; Gang AN; Xin LI; Weiqiang ZHANG; Zhenhua LIU; Nianqin ZHENG; Shengwei CHEN; Wendong ZHAO; Zixiang DI; Zhaojie GU (Dianxin kexue)
The research mainly starts from the development trend of 5G+ satellite integration, and conducts research and analysis on typical domestic and foreign satellite Internet of things/internet solutions, and then leads to application scenarios and services requirement for the development of 5G+ satellite integration, including research and discussion on the technical requirements of 5G satellite space-ground integrated dual-mode terminals, finally, the challenges faced by 5G satellite dual-mode communication terminals are given.With a view to providing industry with guidance on the challenging aspects of standardization and pre-development of 5G+ satellite dual-mode terminals, and to provide useful suggestions and references for overcoming these challenges.